An unusual case of methemoglobinemia resulting from self-administration of nitrobenzene in a psychiatric patient - Chanjal Koonampadan Sathyan; Harihara Sudhan Chidambaram,; Melvin Dominic; Syed Abthahir Sirajudeen; Venkata Durga Prasad Jinka (MGM Journal of Medical Sciences, 2022)
Nitrobenzene, when consumed in large enough doses, can cause methemoglobinemia. By reducing oxygen unloading and oxygen binding, methemoglobinemia reduces oxygen delivery. This is a case of 55-year-old man who is a known case of psychiatric disorder was brought to the emergency room with an alleged history of deliberate consumption of nitrobenzene liquid approximately 10 mL in the morning of the day at his residence. He also instilled 2 drops in the right ear and was taken to a private hospital where the initial management with gastric lavage, multidose activated charcoal and methylene blue was given. He was then referred to the government tertiary care setting for further management. Prompt intravenous methylene blue treatment increases PaO2 in patients with methemoglobinemia.